THE GERMAN SOLUTION OF THE POST-WAR PRICE LEVEL PROBLEM. - Holzer, H. Peter; Schönfeld, Hanns-Martin (The Accounting Review, 1963)
Germany, in recent history, has experienced two serious inflations. Each was a consequence of her defeats in the two World Wars. Germany's industrial capacity survived World War I without suffering serious damages, but a large part of her production was used for reparations and never reached the domestic market. Internal political strife and occupation of a major industrial area by the victorious allied powers further reduced the production available for domestic consumption. During the years of inflation, sound financial reporting was almost impossible. Scholars and practicing accountants examined and experimented with various proposed methods of inflation accounting without discovering any fully satisfactory results. The German balance sheet law of 1948 represents an attempt to achieve uniform balance sheet values at current prices. Although the final results were not ideal, the overall purpose of establishing a new and sound basis for financial reporting and taxation was certainly attained. The financial statements of the years following the currency reform are somewhat distorted because in Germany, as in the United States, price levels have been rising gradually and consistently.